# Summation

We traditionally speak of a sum from i = a to i = b, where b − a is a whole number (0, 1, 2, …); assuming for simplicity that a is an integer (so that b is also), this sum covers every integer i that satisfies the inequality a ≤ i ≤ b, or in other words all of the integers in the interval [a, b]. But in many ways, it's better to think of such a sum as running from i = a to i = b + 1, but with the last item not quite included; that is, the sum covers every integer i that satisfies the inequality a ≤ i < b + 1, or in other words all of the integers in the interval [a, b + 1). Of course, from this perspective, it's not the number b that matters but the number b + 1; if we call this B, then we can write
 Σ a≤i
for what is normally written as
 b Σ . i=a
Note also that it makes perfect sense to have B = a (in other words, b − a = −1); then we are adding up no terms, and the sum is 0.

One nice consequence is that the number of terms in the sum is simply B − a rather than b − a + 1. Perhaps more importantly, we have this theorem:

 Σ + Σ = Σ , A≤i
which looks nicer than
 b c c Σ + Σ = Σ . i=a i=b+1 i=a

The formulas for summing cubic polynomials also tend to be slightly simpler. With the traditional numbering, we have these (from the textbook):

• The sum, from i = 0 to i = b, of a constant c is c(b + 1).
• The sum, from i = 0 to i = b, of i itself is b(b + 1)/2.
• The sum, from i = 0 to i = b, of i2 is b(b + 1)(2b + 1)/6.
• The sum, from i = 0 to i = b, of i3 is b2(b + 1)2/4.
With the off-by-1 numbering, we have these:
• The sum, over 0 ≤ i < B, of a constant c is cB.
• The sum, over 0 ≤ i < B, of i itself is B(B − 1)/2.
• The sum, over 0 ≤ i < B, of i2 is B(B − 1)(2B − 1)/6.
• The sum, over 0 ≤ i < B, of i3 is B2(B − 1)2/4.

The upshot of all of this is that, when you see (for example) a sum as i runs from 2 to 5, you might want to think of it as a sum over 2 ≤ i< 6 instead.

It's also handy to have more general formulas for summing cubic polynomials, starting at an arbitrary place rather than at i = 0. With the traditional numbering, we have these:

• The sum, from i = a to i = b, of a constant c is c(b − a + 1).
• The sum, from i = a to i = b, of i itself is (a + b)(b − a + 1)/2.
• The sum, from i = a to i = b, of i2 is (2a2 + 2ab + 2b2 − a + b)(b − a + 1)/6.
• The sum, from i = a to i = b, of i3 is (a2 + b2 − a + b)(a + b)(b − a + 1)/4.
With the off-by-1 numbering, we have these:
• The sum, over A ≤ i < B, of a constant c is c(B − A).
• The sum, over A ≤ i < B, of i itself is (B − A)(A + B − 1)/2.
• The sum, over A ≤ i < B, of i2 is (B − A)(2A2 + 2AB + 2B2 − 3A − 3B + 1)/6.
• The sum, over A ≤ i < B, of i3 is (B − A)(A + B − 1)(A2 + B2 − A − B)/4.

Go back to the course homepage.

This web page was written between 2013 and 2015 by Toby Bartels, last edited on 2015 November 18. Toby reserves no legal rights to it.

The permanent URI of this web page is `http://tobybartels.name/MATH-1600/2015FA/summation/`.